DETERMINANT OF FINANCIAL DISTRESS IN MANUFACTURING COMPANIES - Hermiyetti, Hermiyetti -; Dharmawan, Donny; Mulatsih, Listiana Sri; Alfiana, Alfiana; Anantadjaya, Samuel PD (STMIK Dharma Wacana, 2024)
Financial distress is a picture of a continuous decline in a company's financial performance that needs to be predicted and minimized. The occurrence of financial distress begins with a decline in the company's financial condition which begins with the company's inability to meet its short-term obligations. The purpose of this study is to determine and evaluate the effect of Return on Assets (ROA), company size and also Debt to Equity Ratio (DER) on financial distress. Regression analysis and quantitative methods are used in the research process. Manufacturing companies that consistently release their financial reports during 2019-2022 and are listed on the Indonesia Stock Exchange are examples. The sampling method used in this study was purposive sampling and succeeded in obtaining 40 samples from 10 companies. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of this study indicate that ROA has a significant effect on financial distress. Meanwhile, company size and DER do not affect financial distress in manufacturing companies in the 2019-2022 period. The implications of the results of this study for manufacturing company management can be an indicator of corrective actions before the company experiences financial distress or has the potential to go bankrupt.